Cardanthera pinnatifida Benth. - a New Record for Northern India - Dixit, S. N.; Siddiqui, M. O. (Indian Forester, 1966)
Cardanthera pinnatifida Benth., an aromatic herb of the family Acanthaceae, has been recorded only from South Konkan and Deviman Ghats (North Kanara). However, recently the authors have observed a very rich and luxuriant growth of this plant in Pokharbhinda, a village about 20 km east of Gorakhpur City. The plant is believed to be an effective blood purifier and, therefore, a detailed pharmaceutical study is suggested.